Living standards in North Ossetia-Alania through the prism of economic processes - Dobronosov Vitaly; Tebieva Delyara; Kebalova Lyubov’ (Bulletin of Geography. Socio-Economic Series)
The paper reflects the dynamics of changes in standard of living in the Republic of North Ossetia-Alania during the post-Soviet period.